Relationships between weekly changes in salivary hormonal responses and load measures during the pre-season phase in professional male basketball players - Kamarauskas, P.; Lukonaitiene, I.; Kvedaras, M.; Venckunas, T.; Conte, D. (Biology of Sport, 2023)
The aim of this study was to assess the relationships between weekly changes in external and internal load considered separately and jointly and salivary hormonal responses during the pre-season phase in professional male basketball players. Twenty-one professional male basketball players (mean ± standard deviation, age: 26.2 ± 4.9 years; height: 198.7 ± 6.7 cm; body mass: 93.2 ± 10.0 kg) were assessed during 5 weeks of the pre-season phase. External load was measured using microsensors and reported as PlayerLoad (PL) and PL/ min. Internal load was calculated using the session rating of perceived exertion scale (sRPE-load), summated heart rate zones (SHRZ) and percentage of maximal heart rate (%HRmax). Salivary hormone responses weremonitored weekly by measuring testosterone (T), cortisol (C), and their ratio (T:C). The relationships between weekly changes in load measures considered separately and jointly and hormonal responses were assessed using linear mixed model analysis. No significant (p > 0.05) relationships were evident between weekly changes in T, C or T:C with external and internal load measures considered separately (R2-conditional = < 0.001-0.027) or jointly (R2-conditional = 0.028-0.075). Factors other than measured loads might be responsible for weekly changes in hormonal responses and therefore external and internal load measures cannot be used to anticipate weekly hormonal responses during the pre-season phase in professional basketball players.